PERBANDINGAN KINERJA INVESTASI PADA REKSADANA SAHAM YANG DIKELOLA OLEH MANAJER INVESTASI LOKAL DAN ASING DI INDONESIA - , Desy Tri Cakrie ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Along with the increase Indonesiaâs grade becomes an investment grade country, make the economic condition in Indonesia is getting better. It also a chance to increase the number of investment in Indonesia and it make the capital market as a good choice for investment. When bankâs interest rate decreased, most all of investor are looking for other alternatives which have higher return. This condition will have good influence in long term for stock market in Indonesia. Based on return and risk of the investment, equity mutual fund is an attractive choice for investor. During the period 2009-2011, Net Asset Value of equity mutual funds have the biggest contribution from the total Net Asset Value of mutual funds in Indonesia. Along with the increase of equity mutual funds investment, which indicated from higher numbers in every year and including the increase of investment managers who managed it in Indonesiaâs capital market, make the investment managerâs reputation become a very important factor. Investment companies need to allocate the portfolio on potential or strategic sectors to optimizing the return. Based on the background, the purpose of this research is to compare the return of equity mutual funds which managed by domestic and foreign investment managers, hence the investor know which one of investment manager type (domestic or foreign) which have the best result or highest return. Performance measurement by calculating 14 samples of equity mutual funds which managed by domestic investment manager and 14 samples of equity mutual funds which managed by foreign investment manager by using methods of Sharpe, Treynor, Jensen and IHSG as a benchmark. From the performance measurement, it will rank from the highest scores to the lowest score of index and make analysis for Top and Worst performance of equity mutual funds. Based on the measurement from 48 samples of equity mutual funds, the result showed good performances (positive index) from all methods of Sharpe, Treynor, Jensen and it dominated by domestic investment managers. From Sharpe and Treynor measurements, there are 20 equity mutual funds or about 71% which have similar rank. A portfolio can be an optimal portfolio if they have similar result, hence it can be concluded that equity mutual funds performance from Sharpe and Treynor measurements are well diversified. But based on percentage from all measurement of Sharpe, Treynor, Jensen, the performance of equity mutual funds overall are underperformed of the market. The best equity mutual fund is the one which have best performance or outperformed of the market. Equity mutual funds which have positive result and in top 10 rank consistently, also well diversified from all of Sharpe, Treynor, Jensen measurements, are from domestic investment managers: Panin Dana Maksima which managed by Panin Asset Management (as the best performance or higher result) and Syailendra Equity Opportunity which managed by PT Syailendra Capital. From the result, we can conclude that the best performance or highest return of equity mutual funds is from domestic investment manager.